Q: What is 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 x 0 plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

X + 1 - x - 1 = 0, for all x. Regroup: (x - x) + (1 - 1) = 0 + 0.

x^2 + x = 0 x(x+1) = 0 x = 0 and x = -1

x = -1/2 or -5 2x2 + 11x + 5 = 0 ⇒ (2x + 1)(x + 5) = 0 ⇒ (2x + 1) = 0 → x = -1/2 or (x + 5) = 0 → x = -5

(x + 6)(x + 1) = 0 so x = either -1 or -6

x2 + 4x + 3 = 0 (x + 1)(x + 3) = 0 x ∈ {-3, -1}

Related questions

2 x 0 x 1 + 1 = 0 + 1 = 1

X + 1 - x - 1 = 0, for all x. Regroup: (x - x) + (1 - 1) = 0 + 0.

x^2 + x = 0 x(x+1) = 0 x = 0 and x = -1

x = 0

x^2 + 1 = 0 x^2 - (-1) = 0 x^2 - i^2 = 0 (x - i)(x + i) = 0 x = i or x = -i

x = -1/2 or -5 2x2 + 11x + 5 = 0 ⇒ (2x + 1)(x + 5) = 0 ⇒ (2x + 1) = 0 → x = -1/2 or (x + 5) = 0 → x = -5

(x + 6)(x + 1) = 0 so x = either -1 or -6

x2 + 4x + 3 = 0 (x + 1)(x + 3) = 0 x ∈ {-3, -1}

x2+12x+11=0 (x+11)(x+1)=0 x=-11 or x=-1

x= -1 answer: 0

It is: 50*50*0+1 = 1

...if you did not recognize this to be (x - 1)^2... x^2 - 2x + 1 = 0 or x^2 - x - x + 1 = 0 x(x - 1) - 1(x -1) = 0 (x - 1) (x - 1) = 0 x = 1